2016
DOI: 10.1103/physreve.93.032127
|View full text |Cite
|
Sign up to set email alerts
|

Thermal rectification and negative differential thermal conductance in harmonic chains with nonlinear system-bath coupling

Abstract: Thermal rectification and negative differential thermal conductance were realized in harmonic chains in this work. We used the generalized Caldeira-Leggett model to study the heat flow. In contrast to most previous studies considering only the linear system-bath coupling, we considered the nonlinear system-bath coupling based on recent experiment [Eichler et al., Nat. Nanotech. 6, 339 (2011)]. When the linear coupling constant is weak, the multiphonon processes induced by the nonlinear coupling allow more phon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 121 publications
(177 reference statements)
0
15
0
Order By: Relevance
“…6,7,17,[28][29][30] Thermoelectric energy conversion has been another. 6,31 Nonlinear effects such as heat current rectification [32][33][34][35][36] and negative thermal resistance have been demonstrated, [37][38][39] and possible ways to control heat transport in molecular junctions have been discussed 40,41 . In addition to these advancements in charge transfer reactions across molecular junctions, emergent experimental and theoretical methods examining the possibility to control electron transfer (ET) in specific vibrational modes [42][43][44] have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,17,[28][29][30] Thermoelectric energy conversion has been another. 6,31 Nonlinear effects such as heat current rectification [32][33][34][35][36] and negative thermal resistance have been demonstrated, [37][38][39] and possible ways to control heat transport in molecular junctions have been discussed 40,41 . In addition to these advancements in charge transfer reactions across molecular junctions, emergent experimental and theoretical methods examining the possibility to control electron transfer (ET) in specific vibrational modes [42][43][44] have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…This result is also an advance with respect to those previously obtained with the 3D coupled FK and FPU lattice system [18], which presents no rectification whatsoever for temperatures above T 0 = 0.12. Nevertheless, a readily available possibility for increasing the rectification efficiency of the 3D mass-graded lattice, especially in the low-temperature regime, could be to implement the recently proposed nonlinear system-reservoir coupling [26], which has already been shown to increase the rectification efficiency of the 1D mass-graded anharmonic FPU lattice [27].…”
Section: Discussionmentioning
confidence: 99%
“…Later, a thermal transistor and a thermal logic gate based on it [27,28], a thermal memory [29], and thermal shuttling [30] are also realized in nonlinear lattices, which can provide powerful tools to manipulate heat transfer and the possibility to do phonon computing like electronic computers [12]. In addition, it's found that thermal rectification can exist in linear lattices with nonlinear system-bath coupling [31], and complex networks with anharmonic interactions [32,33] as well. In experiments, Chang et al [34] fabricated a thermal diode based on the solitonic transport behavior of phonons in carbon nanotubes or boron nitride nanotubes with mass gradient, and the rectification ratio can reach 7%.…”
Section: Introductionmentioning
confidence: 99%